2013
DOI: 10.1021/ef4012388
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Biochar Yield and Heat Required during Pyrolysis of Two-Phase Olive Mill Waste

Abstract: The present study analyzes the effect of several operating factors (initial sample mass, heating rate, conditions of the crucible, and inorganic matter content) on the pyrolysis of two-phase olive mill waste. Simultaneous TGA−DSC measurements were performed according to a one-half fractional factorial design to obtain statistically significant conclusions. The results from this screening design pointed out that the behavior of the TPOMW pyrolysis process is statistically affected to a greater or lesser extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It was reported that the inorganic matter, especially alkali metals (i.e., K, Na, etc.) that represent the ash content, can play a crucial role in shifting the balance in favor of heat release because of its catalytic effect, which simultaneously reduces the energy requirements for the volatilization of biochemical compounds and promotes the exothermic secondary char formation . Therefore, it could be suggested that the high ash content in AG (9.1 wt %) has promoted BC-forming reactions in account of decomposition reactions.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the inorganic matter, especially alkali metals (i.e., K, Na, etc.) that represent the ash content, can play a crucial role in shifting the balance in favor of heat release because of its catalytic effect, which simultaneously reduces the energy requirements for the volatilization of biochemical compounds and promotes the exothermic secondary char formation . Therefore, it could be suggested that the high ash content in AG (9.1 wt %) has promoted BC-forming reactions in account of decomposition reactions.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting finding is the fact that the highest devolatilization rate for tests conducted at 40°C min − 1 was reached at a lower temperature, in comparison with the case of the samples pyrolyzed at 5°C min −1 (around 280°C and 305°C, respectively). Usually, pyrolysis profiles shift to a higher temperature region when heating rate is increased, due to the fact that the heat required for devolatilization is reached later at higher temperatures (i.e., heat transfer limitations) [40][41][42][43][44][45]. Thus, the observed result suggests that an increase from 5 to 40°C min −1 could lead to a faster release of Table 2 Matrix of the factorial design adopted to analyze the pyrolysis behavior of RDF.…”
Section: Resultsmentioning
confidence: 99%
“…According to these results, the production yields of BC and AcBC varied from 31% to 43% of the initial dry weight. These variations in the mass yields were due to the effect of chemical catalysts on volatilization and solid formation reactions (Manyà et al 2013). For the unactivated biochar (BC), the production yield was 6% higher than the 28% yield reported by Francavilla et al (2014).…”
Section: Macroalgae Residue Composition and Biochar Productionmentioning
confidence: 95%
“…In addition, it was reported that during biomass pyrolysis, inorganic matter, especially alkali metals (i.e., K, Na, etc. ), can catalyze both biomass decomposition and biochar-forming reactions (Manyà et al 2013).…”
Section: Macroalgae Residue Composition and Biochar Productionmentioning
confidence: 99%